Analysis of Using Intergovernmental Transfers and Local Own-Source Revenue on Poverty Reduction: Islamic Economics Perspective - Humaira, Annisa; Azzuhra, Alfia; Awang Darmawan Putra (EKOBIS SYARIAH, 2025)
In Islam, the income of a region is based on the principles that must be followed to achieve falah, which improves the welfare of the community. The fulfillment of maqasid al-shariah in a region can be measured by how well regional revenues are used to achieve the basic objectives of Islamic law. This study examines the influence of Intergovernmental Transfers (TKD) and Local Own-Source Revenue (PAD) on the reduction of poverty rates in Pidie district. This study aims to look at the analysis of using TKD and PAD in Pidie Regency on the reduction of poverty rates in the perspective of Islamic economics. The data used are data on the number of realization of TKD revenues, the number of realization PAD revenues, and the percentage of poverty in Pidie Regency with a span of time from 2014 to 2023. The results of the study showed that TKD had a negative and significant effect on poverty, while PAD had a negative but not significant effect. Simultaneous tests showed that the TKD and PAD variables had a negative and significant effect on the poverty rate in Pidie Regency.